2015
DOI: 10.1039/c5cc06920c
|View full text |Cite
|
Sign up to set email alerts
|

CF3-Substituted semisquarate: a pluripotent building block for the divergent synthesis of trifluoromethylated functional molecules

Abstract: The first synthesis of a CF3-substituted semisquarate was accomplished via nucleophilic trifluoromethylation using CF3SiMe3 and subsequent rhenium-catalyzed allylic alcohol rearrangement. The short-step skeletal-divergent synthesis of trifluoromethylated functional molecules was successfully achieved using the CF3-substituted semisquarate as the platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Notably, we recently found that the alkylidenecyclobutenone 1k [ 54 ] was a highly reactive compound and could be easily used in ring-opening and ring expansion with Grignard reagents, organolithium species, primary amines, and water [ 55 ], in which the four-membered ring was easily broken by the nucleophilic reagent. Interestingly, we found that the four-membered ring was stable in the trifluoromethylation reaction [ 56 ] and the desired products 5j or 5k were isolated in promising yields. The structure of the novel compound 5k was unambiguously confirmed by X-ray diffraction analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we recently found that the alkylidenecyclobutenone 1k [ 54 ] was a highly reactive compound and could be easily used in ring-opening and ring expansion with Grignard reagents, organolithium species, primary amines, and water [ 55 ], in which the four-membered ring was easily broken by the nucleophilic reagent. Interestingly, we found that the four-membered ring was stable in the trifluoromethylation reaction [ 56 ] and the desired products 5j or 5k were isolated in promising yields. The structure of the novel compound 5k was unambiguously confirmed by X-ray diffraction analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 A rhenium-assisted rearrangement has also been used in the synthesis of semisquarates. 18 Trifluoroacetic acid has also been used to isomerize allylic alcohols, and this method has been applied to the synthesis of valerenic acid, which binds to both the GABA A and 5-HT 5A receptors, and is used as a treatment of insomnia. 19 Acid-assisted allylic alcohol rearrangement was also used in the synthesis of two quinolone natural products isolated from Pseudonocardia sp.…”
Section: Introductionmentioning
confidence: 99%
“…A divergent synthesis is a strategy aiming to improve the efficiency of chemical synthesis and generate a library of natural compounds from one common versatile synthetic intermediate with a set of reactions. This strategy is rather popular in modern organic synthesis as it permits rapid divergence to a large number of new compounds . Abad's group, Baran's group, and Liu's group have reported the efficient divergent total synthesis of atisane‐type diterpenoids.…”
Section: Introductionmentioning
confidence: 99%